Удмуртская народная кухня - Соковнин Герман Иванович (Удмуртия, 2020)
Экземпляры: (20201008) / Инвентарный номер: 41614 / Цена: 9600.00 / Сис.шифр: 36.997(2=664.1) / Авт.знак: С 59 / ГРНТИ: 65 / ББК: 36.997(2=664.1)